THE NEW APPROACH ON FOOD QUALITY: AN IMPORTANT FACTOR ON CONSUMER BEHAVIOR AND TRENDS IN FOOD QUALITY - Johana Paluchová (Polityki Europejskie, Finanse i Marketing)
The article points at food quality of European products in some points, how could be the each European companies successful in the global competitive situation not only with history or culture but be safety in the area of product quality such as important factor of consumer behavior and. Food quality is an important food manufacturing requirement, because food consumers are susceptible to any form of contamination that may occur during the manufacturing process. Many consumers also rely on manufacturing and processing standards, particularly to know what ingredients are present, due to dietary, nutritional requirements (kosher, halal, vegetarian), or medical conditions (e.g., diabetes, or allergies) and because of the article shows some of new trends at food market in Europe. The provision of safe food which protects customers’ integrity and provides consumers with the desired taste is expected to remain the major priority in world food markets in the foreseeable future. While reducing microbial contamination, chemical contaminants and pesticide residues will gain in importance, ethical products and functional foods are the emerging priorities. Food businesses will need to give much greater attention towards minimising water use and pollution, more sustainable production systems, worker welfare and waste management. Recyclable packaging, conservation and biodiversity, food miles and reducing salinity and land degradation are the emerging environmental issues. Country-of-origin is perceived to be the most important indicator of food quality both now and in the foreseeable future. Identifying which food preservatives, food colourings and flavour enhancing compounds have been used in the food will continue to grow in importance as consumers move towards more natural, unadulterated food products. Identifying the presence of potential allergens is critically important for the growing number of susceptible consumers. The food energy content and the use of sugar and artificial sweeteners are the emerging issues, with the presence of genetically modified organisms and ecolabelling poised to become more prominent in the long-term.